1995
DOI: 10.1182/blood.v86.9.3468.bloodjournal8693468
|View full text |Cite
|
Sign up to set email alerts
|

Retention of glycoprotein Ib/IX receptors on external surfaces of thrombin-activated platelets in suspension

Abstract: The present study has evaluated the hypothesis stating that glycoprotein (GP) Ib/IX, the receptor for von Willebrand factor (vWF), is downregulated and cleared from exposed surfaces to channels of the open canalicular system (OCS) on platelets activated by thrombin in suspension. Cryosections of resting and thrombin-activated platelets fixed at intervals of 1 to 30 minutes after stimulation by thrombin and stained with antiglycocalicin antibody and protein A gold showed no decrease in the density of GPIb/IX re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Results of the present investigation have shown that GPIb receptors are homogeneously distributed on external and internal membranes of resting platelets. A similar concept was suggested by early studies, [12][13][14][15][16][17] but the difficulty in labeling GPIb on membranes in narrow channels of the OCS limited a final conclusion. The extensive system of dilated OCS channels and large membrane complexes in giant platelets from patients with the May-Hegglin anomaly 31,32 and Epstein's syndrome 33 made them suitable candidates for evaluating the distribution of GPIb on resting platelet membranes.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Results of the present investigation have shown that GPIb receptors are homogeneously distributed on external and internal membranes of resting platelets. A similar concept was suggested by early studies, [12][13][14][15][16][17] but the difficulty in labeling GPIb on membranes in narrow channels of the OCS limited a final conclusion. The extensive system of dilated OCS channels and large membrane complexes in giant platelets from patients with the May-Hegglin anomaly 31,32 and Epstein's syndrome 33 made them suitable candidates for evaluating the distribution of GPIb on resting platelet membranes.…”
Section: Discussionmentioning
confidence: 60%
“…Some authors have found that the density of labeling for GPIb within the OCS is less than that observed on the platelet surface. 15,16 Other workers have failed to note significant differences, 12,17 whereas some using enzyme-linked immunsorbent assay techniques with monoclonal antibodies have predicted a large internal pool of GPIb that could replenish any amount of GPIb lost from the external membrane. 18 The latter authors estimated the number of internal copies of GPIb was 3 to 4 times greater than the number of GPIb molecules present on the platelet surface, figures relatively higher than those estimated for GPIIb-IIIa.…”
mentioning
confidence: 99%
“…Immunoelectron microscopy has shown that this loss is associated with an accumulation of GPIb–IX–V within the SCCS, a membrane system that ramifies throughout the platelet [15,35]. Nevertheless, a transitional internalization of GPIb in response to stimulation is still controversial [18,25,36]. In our current work, we have used PFA‐fixed platelets to avoid artifactual GPIb movement by receptor cross‐linking, as was already suggested [37].…”
Section: Discussionmentioning
confidence: 98%
“…It came as a surprise when using platelets stimulated by I U/ml thrombin in a medium without Ca2* or in the presence of 5 mM EDTA and a polyclonal antibody to glycocalicin, Escolar et al (32) failed to detect any changes in the surface density of GP Ib either by immunogold staining and electron microscopy or by flow cytometry. White et al (33) reported likewise following the immunolabelling of cryosections of platelets stimulated with lower doses of thrombin for up to 30 min. Furthermore, when platelets were preincubated with two murine MoAbs to GP Ib, AP-1 and 6D1, prior to their activation with thrombin, the bulk of the murine antibodies remained on the surface (34).Nevertheless, White and his coworkers then reported that when platelets in an EDTA-containing buffer were stimulated by thrombin and analyzed by flow cytometry, the binding of MoAbs to Gp Ib decreased by 60-8070 (35) (also see below).…”
mentioning
confidence: 86%